Le bénévolat, une porte d’entrée privilégiée pour mobiliser les jeunes dans des activités d’apprentissage propices au développement de compétences transversales - Sandrine Cortessis; Saskia Weber Guisan (Éducation et Socialisation)
The research presented in this article examines the involvement of young people aged between 16 and 25 in voluntary work within various types of non-profit organisations. Through thirty semi-structured interviews, we are asking ourselves how young people engage in activities that are neither paid nor compulsory; how and why they commit themselves to this type of activities and finally, how non-profit organisations can potentially be a place for competences development. In focusing first on these young volunteers’ careers and then on the resources offered to them within non-profit organisations, we explore a context of informal learning which allows, under certain conditions, the development of so-called soft skills.